FAKTOR-FAKTOR YANG MEMPENGARUHI SKEPTISME PROFESIONAL AUDITOR - Attamimi, Fikri Muhammad; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to analyze the influence of competence, Time budget Pressure, auditsâ experience, ethic, independency to the scepticism of professional auditor. The respondents of this research are staff auditors (manager, partner, senior, and junior auditor), on the Public Accounting Office (KAP) in Surabaya. The sample collection has been done by using purposive sampling method which is the sample collection technique is based on the certain criteria. The multiple linear regressions analysis are used as the analysis technique. The result of this research shows that the competency has positive influence to the scepticism of professional auditor. The auditorâs experience has positive influence to the scepticism of professional auditor. The ethic has positive influence to the scepticism of professional auditor. The independecy has positive influence to the scepticism of professional auditor. While time budget pressure has a negative influence to the scepticism of professional auditor.Keywords: Competency, Time Budget Pressure, Experience, Ethic and Independency, Scepticim of Professional Auditor.